Negotiating Film Culture: at the Origins of Einaudi’s Publications on Cinema (1948-1952) - Marco De Cristofaro (Cinergie)
This article examines the early development of Einaudi’s cinematic publishing (1948–1952) by tracing editorial negotiations, intellectual exchanges, and institutional constraints that shaped the selection and rejection of books on cinema. Through an extensive analysis of archival correspondence, editorial minutes, and publication catalogs, the study reconstructs the network of translators, consultants, and critics who contributed to establishing a dedicated space for cinema within Einaudi’s catalog. The investigation focuses on figures such as Bruno Fonzi, Antonio Giolitti, Antonio Pietrangeli, Umberto Barbaro, Carlo Ludovico Ragghianti, and Guido Aristarco, as well as key foreign authors whose works defined the publisher’s editorial approach to cinema. The research highlights the ideological, aesthetic, and commercial factors that influenced Einaudi’s choices, revealing tensions between its pedagogical mission and the emerging industrial dynamics of film publishing. By addressing the conflicts between different conceptions of film criticism – ranging from historical-theoretical studies to collections of screenplays – the article sheds light on how Einaudi positioned itself as a platform for intellectual debate on cinema. Ultimately, this study contributes to broader discussions on the intersection between publishing and cinema, demonstrating how the Turin-based house played a crucial role in shaping Italian film culture in the postwar period.